The Effect OfGoods Prices And Buyer Trust On The E-Commerce Sales System For Purchasing Goods Online - Aloysius Rangga Aditya Nalendra; Slamet Heri Winarno; Agus Priadi; Elpa Hermawan; Martinus Wahyu Purnomo; Arman Syah Putra (International Journal of Science, Technology & Management, 2021)
E-commerce is a payment system that is currently booming with e-commerce, so all sales systems that were offline go online and sales systems that were only in one region can be around the world without time limits and where development is compressed so high that it causes There are many changes from the traditional sales system to the internet. Therefore, this study will determine the effect of goods prices and buyer trust on the e-commerce sales system for purchasing goods online. The method used in this research is quantitative methods using a questionnaire that will be distributed in order to obtain data that can be used as research data so that the data can be used as a reference for current research and future research using the questionnaire method so that we will be able to get real data in the field because it is based on data directly obtained from e-commerce customers. The e-commerce system has begun to be developed in the 2000s but has not been used maximally but after the Covid 19 pandemic, now the e-commerce sales system has been very, very developed because of the limitations of the place and time of the Covid 19 pandemic resulting in the prohibition of physical contact. from sellers and buyers, therefore the e-commerce system speaks to the problems that already exist today with the existence of e-commerce so that sellers and buyers can still transact with online media. In this study will be able to produce data that can answer the problem in this research in this study will answer the problem of how the relationship between low prices and customer trust in the e-commerce sales system based on online shopping with online media, therefore this research will use quantitative methods. as an appropriate research method.